Proses Manajemen Peserta Didik dalam Membentuk Karakter Religius - Giantomi Muhammad; Aan Hasanah; Bambang Samsul Arifin (Jurnal al-Thullab, 2021)
This research was conducted to examine the process of student management as an effort to form the religious character for students. The importance of knowing the management of students as a concrete step in preparing the educational process that supports achievement in the formation of the character of students in schools. The number of cases of character retardation that occur today is caused by one of them not considering the student management process that is following the objectives of the implementation process in shaping the character that the school wants to achieve in the implementation of the ongoing educational process. Religious character is a character that is expected, one of which is in the educational process at school, religious character has a major impact on the progress of students. Therefore, this study aims to examine the process of student management in schools in shaping the religious character of the personality of students. This research uses a qualitative method with a case study approach, data collection techniques with interviews, and data analysis techniques are carried out. The research location will be conducted at SMA PGII 2 Bandung. The results and discussion of this research will be carried out in the form of a description of the supporting theories, an in-depth study of the management process of students informing religious characters. Penelitian ini dilakukan untuk mengkaji proses manajemen kemahasiswaan sebagai upaya pembentukan karakter religius bagi mahasiswa. Pentingnya mengetahui manajemen siswa sebagai langkah konkrit dalam mempersiapkan proses pendidikan yang mendukung pencapaian dalam pembentukan karakter siswa di sekolah. Banyaknya kasus keterbelakangan karakter yang terjadi saat ini salah satunya disebabkan oleh tidak memperhatikan proses pengelolaan siswa yang mengikuti tujuan dari proses implementasi dalam membentuk karakter yang ingin dicapai sekolah dalam pelaksanaan proses pendidikan yang sedang berlangsung. Karakter religius merupakan karakter yang diharapkan, salah satunya dalam proses pendidikan di sekolah, karakter religius berdampak besar terhadap kemajuan siswa. Oleh karena itu, penelitian ini bertujuan untuk mengkaji proses manajemen siswa di sekolah dalam membentuk karakter religius kepribadian siswa. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus, teknik pengumpulan data dengan wawancara, dan teknik analisis data yang dilakukan. Lokasi penelitian akan dilakukan di SMA PGII 2 Bandung. Hasil dan pembahasan penelitian ini akan dituangkan dalam bentuk uraian tentang teori-teori pendukung, kajian mendalam tentang proses pengelolaan pendidikan karakter religius peserta didik.